PARTISIPASI KARYAWAN DAN PIMPINAN DIVISI QUALITY CONTROL DALAM PENYUSUNAN ANGGARAN PADA PT. DELTA PASIFIC INDOTUNA - Serina, Alexander; Nabila; Solagracia Malumbot; Venny P. Tatauhe; Rivaldy Dompas; Feiby N. Wantah; Monika I. K. Sukanto (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2024)
This study aims to analyze and understand the role of employee participation and leadership in the Quality Control (QC) Division in the budgeting process at PT. Delta Pasific Indotuna Bitung. Budgeting is a crucial aspect of a company's financial management system, serving as a tool for planning, coordinating, and controlling organizational activities. The research method used was descriptive qualitative, with a case study approach through interviews with leaders, supervisors, and QC employees. The results indicate that the budgeting process in the QC Division is participatory and collaborative, with each level playing a role in submitting and evaluating annual budget requirements. QC leaders act as guides and policymakers, while employees provide technical input based on field needs. Open coordination and communication between leaders and staff contribute to the effectiveness of the budgeting process. This active participation positively impacts motivation, a sense of responsibility, and the efficient use of resources in the QC Division. This study recommends that the company maintain a participatory budgeting system and conduct regular evaluations to ensure alignment between planning and operational needs.